Interconnection between electronic commerce and logistics in the context of their accounting and taxation - Kruchak, Lyudmila; Holovachko, Vasyl; Kruchak, Valentyna (Herald of Economics, 2025)
Introduction. In the context of intense competition in electronic business, logistics plays a key role in ensuring the continuity of goods and transport flows and in meeting consumer needs. Integration of logistical, commercial, and informational flows requires an effective accounting framework for managing e-business operations. The need to scientifically substantiate the role of accounting as an informational intermediary between e-commerce and logistics under the conditions of the digital economy defines the relevance of this study. Purpose. The article aims to identify interaction formats between e-commerce and logistics, along with their specific features that influence the methodology and organization of accounting and taxation in the field of electronic business.Results. The interconnection between e-commerce and logistics under the digital economy has been analyzed, with accounting defined as an integrating component in supporting the interests of end consumers across the supply, warehousing, sales, and delivery stages. Four formats of interaction between e-commerce and logistics have been classified, considering accounting and taxation specifics: Intra-organizational logistics (involving detailed warehouse accounting, tracking of delivery costs, cost calculation of logistics services, and separate VAT accrual and payment); Logistics outsourcing (entailing the delegation of accounting and tax functions to external providers and recording of outsourcing service costs); Omnichannel logistics (focused on the integration of commercial and logistical information flows, enabling multi-variant accounting approaches and enhanced communication with clients and logistics operators); Dropshipping (characterized by the absence of warehouse accounting, the constant need to confirm stock availability with suppliers, and taxation minimization). Selection of the interaction format depends on business size, product type, market share, and enterprise strategy.Prospects. The implementation of autonomous robotic transport for goods delivery transforms traditional formats into hybrid models of e-commerce and logistics integration. The necessity to improve accounting and taxation methods for these hybrid formats highlights the importance of continued scientific research and practical developments in the field of electronic business.